Electrochemical Degradation of Reactive Red 195 from its Aqueous Solution using RuO2/IrO2/TaO2 Coated Titanium Electrodes - Umadevi, M.; Rathinam, R.; Poornima, S.; Santhi, T.; Pattabhi, S. (Asian Journal of Chemistry, 2021)
The electrochemical oxidation of reactive red 195 from aqueous solution was carried out using titanium electrode in an electrochemical cell reactor. The effect of different operating parameters such as dye concentration, current density, electrolyte concentration, pH and stirring speed were investigated. The UV-visible spectroscopy confirmed the removal and degradation of reactive red 195. Three different supporting electrolytes such as NaCl, NaNO3 and Na2SO4 were used for electrolysis and NaCl were found to be effective for the removal of reactive red 195 dye from its aqueous solution. The maximum percentage of colour removal was 94%, under the optimum operating conditions with electrolyte (NaCl) concentration 0.075 M, current density 25 mA/cm2, pH 5 and stirring speed of 250 rpm. This method was found to be relatively more effective to the conventional treatment techniques.